Uncontrolled Blood Pressure and Associated Factors Among Persons With Diabetes: A Community Based Study From Kerala, India - Sreedevi, Aswathy; Krishnapillai, Vijayakumar; Menon, Vishnu B.; Mathew, Minu Maria; Nair, Rajeesh R.; Pillai, Gopal S.; Numpelil, Mathews; Menon, Jaideep; Marwaha, Vishal (Frontiers in Public Health, 2022)
Co-existence of raised blood pressure in people with Type 2 Diabetes Mellitus is a major contributor to macrovascular and microvascular complications. The aim of our study was to determine the prevalence of uncontrolled blood pressure and its associated factors in persons with Type 2 Diabetes Mellitus (T2DM) in a district in Kerala. Methods The study was conducted in Ernakulam district in Kerala and a total of 3092 individuals with T2DM were enrolled after obtaining consent. Those with a blood pressure ‘above or equal to 140mmHg’ and or ‘above or equal to 90mm Hg’ were thus considered to have uncontrolled blood pressure. Basic demographic details were collected, along with HbA1c estimation and screening for diabetic retinopathy, peripheral arterial disease (PAD), and peripheral neuropathy. The model for determinants of uncontrolled blood pressure was developed adjusting for age, gender, education,duration of Diabetes, occupation and body mass index(BMI). Results Mean age of study population was 59.51 ± 9.84 years. Mean duration of T2DM was found to be 11.3 + 6.64 years. The proportion of uncontrolled HTN adjusted for clustering was 60% (95% C.I. 58%,62%). Among them only one in two persons (53.3%) had history of Hypertension. Age >60 yrs (aOR 1.48, 95% CI 1.24,1.76; p<.001), unemployment (aOR 1.33, 95% CI 1.01,1.75; p<.01), duration of Diabetes >11yrs (aOR 1.42, 95% CI 1.19,1.68; p<.001), BMI > 23 (aOR 1.33, 95% CI 1.10,1.59; p<.002), were found to be independent determinants of high blood pressure levels when adjusted for the aforementioned variables, gender, education and cluster effect. The association between complications such as peripheral neuropathy, peripheral arterial disease and retinopathy showed a higher risk among those with uncontrolled blood pressure. Retinopathy was 1.35 times more (95% CI1.02,1.7, p<.03), PAD was 1.6 times more (95% CI 1.2,2.07, p<.001) and peripheral neuropathy was 1.5 (95% CI 1.14,1.9, p<.003) times more compared to their counterparts. Conclusion Target blood pressure levels were far from being achieved in a good majority of the persons with T2DM. To reduce further macrovascular and microvascular events in people with T2DM, effective awareness and more stringent screening measures need to be employed in this population.